Pemanfaatan iSpring Suite 9 Dalam Pembelajaran Fisika Di SMAN 1 Gunung Meriah - Malahayati Malahayati; Fathiah Fathiah; Fathurrahman Fathurrahman; Arika Dhien Sartika (PTE FTK UIN Ar-Raniry, 2022)
The development of information technology has given positive changes to the field of education. The leak mastery of technology both in terms of designing or implementing learning results caused less teacher competence and the achievement of student learning outcomes. Utilization of iSpring Suite application is based on the limitations of teachers in designing and compiling learning media. Thus, teachers are required to be able to adapt to the use of digital technology in the world of education. This study aims to facilitate the evaluation of Physics learning by using the iSpring Suite software which used laptop as a server (local hosting) and displaying student scores without the teacher checking manually. In addition, the iSpring Suite could also be used to create learning media in the form of an attractive ebook with available features. The method used in this study is a quantitative method. The sample in this study consisted of three classes, two experimental classes, namely XI IPA 3, XI IPA 4 and one control class, namely XI IPA 2. The data was collected by using interviews, test questions and student response questionnaires. The result of students' responses to ebooks and iSpring Suite-assisted evaluation proved that 79% in class XI IPA 3 agreed. Based on the data, it can be concluded that iSpring Suite can be used as an alternative application in making media and material evaluation quizzes. It is also recommended that this application can be continued its application to other subjects.